2021
DOI: 10.1039/d1tc02961d
|View full text |Cite
|
Sign up to set email alerts
|

Ferroic phase transitions and magnetoelectric coupling in cobalt doped BaTiO3

Abstract: Magnetoelectric (ME) materials exhibit interesting physics with cross coupling between ferroelectric and magnetic order parameters and thus the strong potential to be utilized in memory, spintronics and other multifunctional electronic/magnetic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…So, coupling between the broad CP and the A 1 (1LO) mode may be the origin of Fano resonance of the BCT ceramic. Recently, Pradhan et al [60] reported the physical origin of Fano resonance of Co-doped BT is the coupling between a discrete A 1 (LO 1 ) phonon around 173 cm -1 and the broad CP, due to rapid polarization fluctuations in PNRs.…”
Section: B Raman Spectroscopymentioning
confidence: 99%
“…So, coupling between the broad CP and the A 1 (1LO) mode may be the origin of Fano resonance of the BCT ceramic. Recently, Pradhan et al [60] reported the physical origin of Fano resonance of Co-doped BT is the coupling between a discrete A 1 (LO 1 ) phonon around 173 cm -1 and the broad CP, due to rapid polarization fluctuations in PNRs.…”
Section: B Raman Spectroscopymentioning
confidence: 99%
“…Recently, modified BTO materials have attracted special attention because they exhibit favorable structural, optical, and electrical properties at low temperatures. , BTO is a promising multifunctional material that can be doped with transition metal ions such as Fe, Ni, Co, and so forth or other impurities for a variety of applications. Typically, a ferroelectric substance can acquire the ferromagnetic property by injecting transition-metal dopants into the ferroelectric system material. , Moreover, pure BTO exhibits lower ionic conductivity and behaves as an insulator at room temperature. According to the defect model, the substitution of double acceptor impurities in titanates at Ti sites and in barium at Ba sites improves both the ionic and electronic conductivities accompanied by the formation of charge carriers and oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, modified BTO materials have attracted special attention because they exhibit favorable structural, optical, and electrical properties at low temperatures. 17 , 18 BTO is a promising multifunctional material that can be doped with transition metal ions such as Fe, Ni, Co, and so forth or other impurities for a variety of applications. 19 21 Typically, a ferroelectric substance can acquire the ferromagnetic property by injecting transition-metal dopants into the ferroelectric system material.…”
Section: Introductionmentioning
confidence: 99%
“…The opposite change trends of a and c lattice parameters lead to the linear increase in the unit cell volume with increasing doping level. 29,30 The increase in the unit cell volume can be due to the significantly larger ionic radius of Co than that of the Ti 4+ ion. When the coordination number is 6, the Co ion can exist in the samples with different spin and oxidation states with different ionic radii: Co 2+ (low spin, 0.65 Å), Co 2+ (high spin, 0.745 Å), Co 3+ (low spin, 0.545 Å), Co 3+ (high spin, 0.61 Å), and Co 4+ (high spin, 0.53 Å).…”
Section: Resultsmentioning
confidence: 99%